Smart home lighting control system using bluetooth based android smartphone / Muhammad Yusuf Jupda - Jupda, Muhammad Yusuf (2014)
A smart home system provides comfort, convenient living, energy saving, safety and security for the users. Using a Bluetooth based smart home Android consumers can control everything in a remote location in short response time. Users easily can switch on and off any electrical devices in their home such as controlling the lighting switching without physical interaction. The purpose of this project is to demonstrate lighting control system concepts using enabled Bluetooth Smartphone with implementing a prototype using relay board. This system using Arduino Uno microcontroller to controlled the relay board by sending the command. Conclusion obtained is this system can help users in order to control the lighting home system more easy and effective.